Kreativitas Anak Usia Dini dan Anak SD Kelas Kecil di Lingkungan RT 14 RW 1 Kedungmundu Semarang - Purwosetiyono, F X Didik; Zuhri, M Saifuddin; Nursyahidah, Farida; Rubowo, Maya Rini (Pelita: Jurnal Pengabdian kepada Masyarakat, 2023)
This PKM (Community Service) activity aims to instill children's activity and creativity in motor activities and skills through training on simple Tangram and Origami media for early childhood and small elementary school through the early childhood and small elementary school mentoring program in the neighborhood of RT 14 RW 1 Kedungmundu Semarang. Tangram and Simple Origami emphasize shapes, train memory, and students' cognitive, affective, and psychomotor aspects, where children are invited to recognize several forms and manipulate these objects, and increase students' abilities to be more creative. With this PKM, early childhood and small elementary school children in RT 14 RW 1 Kedungmundu Semarang get an overview of an activity that provides a playful atmosphere for children (learning while playing) so that children get a more meaningful and enjoyable learning atmosphere. This PKM activity runs in an orderly, smooth, and enthusiastic manner to provide benefits for students, able to apply both independently and in groups in subsequent actions in the RT 14 RW 1 Kedungmundu Semarang and also more expansive environments, providing a variety of learning and creativity for children about Tangram and Simple Origami media, especially early childhood and slight grade elementary school children in their environment. This activity also restores children's learning activities after the Covid-19 pandemic in their neighborhood.